2022
DOI: 10.3390/ijms23105392
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles Formulation Improves the Antifibrogenic Effect of Quercetin on an Adenine-Induced Model of Chronic Kidney Disease

Abstract: Renal fibrosis is the final stage of chronic kidney injury characterized by glomerulosclerosis and tubulointerstitial fibrosis with parenchymal destruction. Quercetin belongs to the most studied flavonoids with antioxidant, anti-inflammatory, antifibrogenic, and antitumor activity. It modifies the TGF-β/Smad signaling pathway, decreasing profibrogenic expression molecules and inducing the expression of antioxidant, anti-inflammatory, and antifibrogenic molecules. However, quercetin exhibits poor water solubili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Interestingly, our findings were in line with [ 79 ], who highlighted the promising antioxidant activity of the encapsulated apigenin for the treatment of hepatocellular carcinoma with an excellent stability and bioavailability. In the same context, the authors of [ 80 ] confirmed that the crystal structure of quercetin nanoparticles demonstrated a higher bioavailability than quercetin itself due to the increased surface area with a higher solubility. Notably, quercetin nanoparticles were able to inhibit the expression of profibrogenic genes.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, our findings were in line with [ 79 ], who highlighted the promising antioxidant activity of the encapsulated apigenin for the treatment of hepatocellular carcinoma with an excellent stability and bioavailability. In the same context, the authors of [ 80 ] confirmed that the crystal structure of quercetin nanoparticles demonstrated a higher bioavailability than quercetin itself due to the increased surface area with a higher solubility. Notably, quercetin nanoparticles were able to inhibit the expression of profibrogenic genes.…”
Section: Discussionmentioning
confidence: 97%
“…Quercetin effectively inhibited the TGF-β/Smad signaling pathway by promoting the expressions of antifibrogenic genes such as Smad6 and Smad7 while inhibiting the expressions of profibrogenic genes such as Col I, TGF-β, Smad3, and α-SMA. Quercetin may activate antifibrogenic and anti-inflammatory signaling pathways to inhibit the formation of an adenine-induced model of chronic kidney disease [ 28 ]. The study demonstrated that tripartite motif-containing 33 (TRIM33) is overexpressed in the lung during fibrotic conditions and plays a protective role against fibrogenesis by inhibiting the TGF-β1 pathway independently of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Nanotechnology has made possible drug-loaded structures that can pass the blood–brain barrier, targeted medication delivery, and increased drug bioavailability ( Gao et al, 2018 ). When quercetin nanoparticles were utilized, the relative oral bioavailability rose by 523%, indicating the possibility of dosage reduction ( Sánchez-Jaramillo et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%